Litteratur, teori, terrorism: Anteckningar om »överskridandet« som tankefigur och problematik - Persson, Magnus (Tidskrift för litteraturvetenskap, 2009)
Literature, theory and terrorism In this paper I chart some of the numerous connections between literature, theory and terrorism. Ever since the emergence of romanticism, the artistic ideal of transgression has played a prominent role in aesthetic theory and practice. In late modernity, however, the notion of transgression has become so common in all fields of culture, that its critical potential must be questioned. This complex issue is discussed here in relation to both literary and theoretical examples.